(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud computing is a sort of technology that now aiming to power next generation data centers and to enable application service providers to lease data center capacities to deploy applications depending on user QoS (Quality of Service) needs. Adopting the cloud computing is like signing the new form of a website. In cloud computing, the GUI that controls it make is directly control the hardware resource and your application. But one of the difficult phase in cloud computing is to deploy in real environment. It is difficult to know the exact cost as well as requirement until and unless we own the service not only that whether it will support the existing applications that is available on traditional data center or had to design a new application for the cloud computing environment. Some of the parameters such as security issue, fault tolerance and latency are need to keen care before deploying that we can enable to know solely before implementation. But by using simulation, we can do the experiment before deploying it to real environment. Simulation provide a way to understand the real environment of cloud computing and after achieving the successful result we can commence deploying application in cloud computing environment. By exploiting the simulator, we can save the time as well as cost also.